2007
DOI: 10.2500/ajr.2007.21.3068
|View full text |Cite
|
Sign up to set email alerts
|

Murine Tracheal and Nasal Septal Epithelium for Air–Liquid Interface Cultures: A Comparative Study

Abstract: To increase the yield of respiratory epithelial cells harvested from mice, we have found that the nasal septum is a far superior source when compared with the trachea. The greater surface area and increased concentration of ciliated epithelial cells has the potential to provide an eightfold increase in epithelial cells for the development of air-liquid interface cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 8 publications
4
61
0
Order By: Relevance
“…Primary lung epithelial cells were isolated from approximately 3-to 4-week-old mice and cultured as previously described (67,68). Briefly, lungs were digested in HBSS containing 10 mg/ml type II collagenase and 20 μg/ml DNase I at 37°C for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Primary lung epithelial cells were isolated from approximately 3-to 4-week-old mice and cultured as previously described (67,68). Briefly, lungs were digested in HBSS containing 10 mg/ml type II collagenase and 20 μg/ml DNase I at 37°C for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…The volume of fluid on apical surface of murine nasal epithelial cells depends on the balance between Na 1 reabsorption (mainly through ENaCs) and Cl 2 secretion (mainly through CFTR) (22 6C). These data indicated that IaI decreased ENaCs but not CFTR (or at least it decreased ENaCs to a much higher extent than CFTR), in agreement with our I sc measurements across ATII cell monolayers ( Figure 3).…”
Section: Iai Increased the Airway Surface Liquid Depth Overlying Primmentioning
confidence: 99%
“…Confluent monolayers of rat ATII cells (17) or murine (C57BL/6) nasal epithelial cells (22) were incubated with IaI (0.1 mg/ml) in 100 ml of Normal Ringers added on their apical side for 2 or 4 hours. Cells were mounted in Ussing chambers, and shortcircuit currents (I sc ) and transepithelial resistances were measured before and after addition of amiloride (10 mM), forskolin (10 mM), and glibenclamide (400 mM) in the apical compartments (21,23,24).…”
Section: Short-circuit Currents Across Atii Cellsmentioning
confidence: 99%
“…Primary cultures of airway epithelia have emerged as a powerful model to study epithelial cell biology and the impact of diseases on tissue function (18,22,39). Cells grown at the air-liquid interface (ALI) form a polarized, pseudostratified columnar epithelium that closely resembles the morphology of the in vivo surface epithelium of the conducting airways (2,18,24,33,63,64), providing an opportunity to study cell biology, disease pathogenesis, and treatments (66).…”
mentioning
confidence: 99%